2012
DOI: 10.1590/s0102-695x2012005000079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, salinity and irradiance on carposporeling development of Hidropuntia caudata (Gracilariales, Rhodophyta)

Abstract: Abstract:The success of seaweed cultivation depends on the scientific control of the tolerance limits and the optimal physiological conditions that affect the spore germination and the early development of algal species. In order to establish cultivation techniques for spores of Hidropuntia caudata (J. Agardh) Gurgel & Fredericq, the effects of irradiance, salinity, and temperature on the carpospore germination and carposporeling development were evaluated under laboratory conditions. Five photon flux densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
3
0
1
Order By: Relevance
“…Indeed, even if G. caudata has been described as euryhaline species (Yokoya and Oliveira ), experiments have shown that it was not able to grow at salinities lower than 15 (de Miranda et al. ) and it can be assumed that strong freshwater outflows may have a significant impact on the fitness of these intertidal populations. The possible role of the São Francisco River as a promoter of differentiation has been commonly reported in terrestrial organisms (Pellegrino et al.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even if G. caudata has been described as euryhaline species (Yokoya and Oliveira ), experiments have shown that it was not able to grow at salinities lower than 15 (de Miranda et al. ) and it can be assumed that strong freshwater outflows may have a significant impact on the fitness of these intertidal populations. The possible role of the São Francisco River as a promoter of differentiation has been commonly reported in terrestrial organisms (Pellegrino et al.…”
Section: Discussionmentioning
confidence: 99%
“…For tropical marine macroalgae, lethal and sublethal temperatures have been recorded between 32 °C and 38 °C (Koch et al 2013) (e.g. Miranda et al 2012;Araújo et al 2014;Castro & Yokoya 2019). The maximum temperature tested in this study (32 °C) was not lethal for either species, although their lowest growth was recorded at this temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira (2002: 390) and Hydropuntia caudata (J. Agardh 1852: 598) C.F.D. Gurgel & S. Fredericq (2004: 155), and consequently, the natural populations of these species are reduced to a few individuals who have lost the ability to recover (Miranda et al 2012).…”
Section: Introductionmentioning
confidence: 99%